Evaluating the Guidance and Counseling Service Program through a Comprehensive CIPP Model Framework Addressing the Strategic Gaps Between Educational Policy and Implementation Effectiveness - Iluminata Novianti; Aunurrahman Aunurrahman; Henny Sanulita; Usman Radiana; Eni Rosnija (Newinera Publisher, 2026)
Guidance and counseling (GC) services occupy a strategic role in supporting students’ academic development, personal–social growth, and career readiness; however, the effectiveness of their implementation in secondary schools still requires systematic evaluation to ensure they meet the demands of modern education. We directed this study to evaluate the GC service program at SMA Negeri 1 Sekadau using the Context, Input, Process, and Product (CIPP) model as a basis for continuous improvement. This research employs a qualitative evaluative approach, weaving together in-depth interviews, field observations, and document analysis to capture the authentic perspectives of school administrators, practitioners, and students. By situating our investigation within the real-world dynamics of the school ecosystem, we aimed to uncover the tensions between policy ideals and operational realities. Our investigation reveals a compelling narrative of a program caught between normative aspirations and operational constraints. We found that while the GC program is formally aligned with national educational policies and the Merdeka Curriculum, its context remains largely reactive, relying on incident reports rather than systematic diagnostic needs assessments. Furthermore, although the school benefits from professionally qualified personnel, they are significantly hindered by structural deficits, specifically a lack of validated service instruments and facility support. The implementation process follows a routine schedule yet is often characterized by administrative informality, lacking the rigorous documentation and collaborative mechanisms necessary for truly reflective practice. Finally, while the services produce initial positive personal-social impacts on students, these outcomes remain largely anecdotal, unmeasured, and unevenly distributed across the student body.